Validity of Reporting Oxygen Uptake Efficiency Slope from Submaximal Exercise Using Respiratory Exchange Ratio as Secondary Criterion - Wilby Williamson; Jonathan Fuld; Kate Westgate; Karl Sylvester; Ulf Ekelund; Soren Brage (Pulmonary Medicine)
Background. Oxygen uptake efficiency slope (OUES) is a reproducible, objective marker of cardiopulmonary function. OUES is reported as being relatively independent of exercise intensity. Practical guidance and criteria for reporting OUES from submaximal tests has not been established. Objective. Evaluate the use of respiratory exchange ratio (RER) as a secondary criterion for reporting OUES. Design. 100 healthy volunteers (53 women) completed a ramped treadmill protocol to exhaustive exercise. OUES was calculated from data truncated to RER levels from 0.85 to 1.2 and compared to values generated from full test data. Results. Mean (sd) OUES from full test data and data truncated to RER 1.0 and RER 0.9 was 2814 (718), 2895 (730), and 2810 (789) mL/min per 10-fold increase in VE, respectively. Full test OUES was highly correlated with OUES from RER 1.0 (r=0.9) and moderately correlated with OUES from RER 0.9 (r=0.79). Conclusion. OUES values peaked in association with an RER level of 1.0. Sub-maximal OUES values are not independent of exercise intensity. There is a significant increase in OUES value as exercise moves from low to moderate intensity. RER can be used as a secondary criterion to define this transition.